Georgia Architectural and Historic Properties Survey of Barwick [014] Bertie St. #14, Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Barwick [014] Bertie St. #14, Quitman, Ga. December 1980. Square plan house. Hipped roof with exposed rafters. Shed porch (screened). Shiplap siding. Sash windows with 2/2 lights. Set on brick piers. Fair condition. Date of Construction: c. 1925. Significant as part of a potential National Register historic district, of 1900's and 1920's houses in the southeast portion of Barwick. See map for reference.
Georgia Architectural and Historic Properties Survey of Barwick [014] Bertie St. #14, Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 950 KB (973,806 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Barwick, Ga.; Quitman (Ga.)